Impact of Unethical Medical Practices on Patients' Socio-Economic Challenges in Peshawar - Muhammad Sheraz,; Dr shakeel Ahmad, (Dialogue Social Science Review (DSSR), 2025)
This research aims to analyze patients' experiences in Peshawar regarding the impact of over-prescription, unnecessary surgeries and costly treatments on their overall well-being. It also seeks to investigate the underlying causes of the high prevalence of unethical medical practices among private physicians in the region. By examining these factors, the study intends to illuminate the adverse effects of such practices on patient health and financial security, while identifying systemic issues that contribute to unethical prescribing behaviors within the local healthcare landscape. This qualitative study employed various research methods to gather data from healthcare providers and patients, selected from diverse socio-economic backgrounds to ensure a wide range of perspectives. The data collection took place at Dabgari Garden Plazas in Peshawar, specifically targeting healthcare facilities such as Khattak Medical Centre, Khyber Medical Centre, Khusal Medical Centre, Ibrahimi Hospital, Akbar Medical Centre, Abaseen Hospital, Habib Medical Centre, and Auqaf Plaza. A total of 30 respondents, including doctors, patients, attendants, touts, pharmaceutical representatives, chemists, pharmacists, laboratory technicians, and X-ray technicians, were interviewed to provide comprehensive insights into the healthcare dynamics at these centers. In line with the qualitative nature of the research, in-depth interviews were conducted to explore nuanced perspectives and insights. Each interview lasted between 20 to 30 minutes, using unstructured questions to encourage open-ended responses, and the sessions were tape-recorded for further analysis. Some participants, such as X-ray and laboratory technicians and their supervisors, were interviewed using thematic questions to delve into their experiences with unethical medical practices. In addition, demographic information was collected to better understand the socio-economic conditions of patients affected by various illnesses, contributing to a deeper understanding of the healthcare environment in these medical centers. The study made an effort to maintain gender balance, with both male and female participants contributing to ensure representation from both genders. This diversity of participants provided comprehensive insights into the healthcare dynamics within the selected medical centers. The investigation into unethical medical practices in Peshawar's Dabgari Garden has revealed alarming findings. Overprescribing medications, driven by the pursuit of profit, is a rampant issue in the area, where some doctors prioritize financial gains over patient health. This practice, often facilitated by deceptive marketing from pharmaceutical companies, leads to prescription deception, where unnecessary or harmful drugs are recommended. Additionally, patients face exorbitantly high consultation fees, further burdening their financial well-being. Profit-driven surgeries have also surfaced as a critical issue, where procedures are suggested or conducted not based on medical necessity, but rather on the surgeon's financial incentives. These high-cost healthcare services have severe socio-economic implications, pushing lower-income patients deeper into financial distress. The influence of pharmaceutical companies on medical practice introduces significant ethical dilemmas, as doctors are swayed by financial incentives to prescribe certain medications. Moreover, referral frauds, where patients are referred to specific hospitals or specialists in exchange for kickbacks, highlight the darker side of healthcare in the region, further eroding patient trust and compromising the integrity of medical practice in Dabgari Garden. The healthcare landscape in Peshawar faces significant challenges stemming from the knowledge gap between doctors and patients, which is exacerbated by poverty, limiting access to essential health information and services. This disparity has contributed to a troubling shift where doctor prescriptions increasingly prioritize pharmaceutical sales over genuine patient care, raising ethical concerns. This is compounded by the unquestioned authority of registered doctors from Pakistan Medical and Dental Colleges, who often operate with impunity in their prescription and surgical practices, undermining the integrity of the healthcare system.